Pengembangan Sistem Manajemen Arsip Digital Berbasis Web untuk Meningkatkan Efisiensi Pengelolaan Arsip - Melandi, Angga; Komul, Theodora Maria Putri (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The digital era requires companies to implement efficient archive management systems to support operational activities and accurate decision-making. Archive management that is not optimally integrated can lead to low operational efficiency, delayed access to information, and increased risks of data loss and management errors. This study aims to develop a web-based digital archive management system to improve the efficiency of archive management in companies by automating the processes of recording, storage, retrieval, as well as archive borrowing and returning, supported by role-based access control. The system was designed using an object-oriented modeling approach, while system testing was conducted using Black-Box Testing and User Acceptance Test (UAT) methods. The results show that the developed system improves archive management efficiency, accelerates information access, and reduces the risks of data loss and management errors, indicating that the system is well accepted and capable of supporting increased productivity in corporate archive management.